Combinatorial optimization of CO2 transport and fixation to improve succinate production by promoter engineering. Issue 7 (3rd February 2016) - Yu, Jun‐Han; Zhu, Li‐Wen; Xia, Shi‐Tao; Li, Hong‐Mei; Tang, Ya‐Ling; Liang, Xin‐Hua; Chen, Tao; Tang, Ya‐Jie
ABSTRACT: To balance the flux of an engineered metabolic pathway to achieve high yield of target product is a major challenge in metabolic engineering. In previous work, the collaborative regulation of CO2 transport and fixation was investigated with co‐overexpressing exogenous genes regulating both CO2 transport ( sbtA and bicA ) and PEP carboxylation (phosphoenolpyruvate (PEP) carboxylase ( ppc ) and carboxykinase ( pck )) under trc promoter in Escherichia coli for succinate biosynthesis. For balancing metabolic flux to maximize succinate titer, a combinatorial optimization strategy to fine‐tuning CO2 transport and fixation process was implemented by promoter engineering in this study. Firstly, based on the energy matrix a synthetic promoter library containing 20 rationally designed promoters with strengths ranging from 0.8% to 100% compared with the widely used trc promoter was generated. Evaluations of rfp and cat reporter genes provided evidence that the synthetic promoters were stably and had certain applicability. Secondly, four designed promoters with different strengths were used for combinatorial assembly of single CO2 transport gene ( sbtA or bicA ) and single CO2 fixation gene ( ppc or pck ) expression. Three combinations, such as Tang1519 (P4 ‐ bicA  + pP19 ‐ pck ), Tang1522 (P4 ‐ sbtA  + P4 ‐ ppc ), Tang1523 (P4 ‐ sbtA  + P17 ‐ ppc ) with a more than 10% increase in succinate production were screened in bioreactor. Finally, based on the above results, co‐expression of the four transport and fixation genes were further investigated. Co‐expression of sbtA, bicA, and ppc with weak promoter P4 and pck with strong promoter P19 (AFP111/pT‐P4 ‐ bicA ‐P4 ‐ sbtA  + pACYC‐P19 ‐ pck ‐P4 ‐ ppc ) provided the best succinate production among all the combinations. The highest succinate production of 89.4 g/L was 37.5% higher than that obtained with empty vector control. This work significantly enhanced succinate production through combinatorial optimization of CO2 transport and fixation. The promoter engineering and combinatorial optimization strategies used herein represents a powerful approach to tailor‐making metabolic pathways for the production of other industrially important chemicals. Biotechnol. Bioeng. 2016;113: 1531–1541. © 2016 Wiley Periodicals, Inc. Abstract : For balancing metabolic flux to maximize succinate titer, a combinatorial optimization strategy to fine‐tuning CO2 transport and fixation process was implemented by promoter engineering in this study. Four designed promoters with different strengths were used for combinatorial assembly of CO2 transport genes ( sbtA and bicA ) and CO2 fixation genes ( ppc and pck ) expression. Co‐expression of sbtA, bicA, and ppc with weak promoter P4 and pck with strong promoter P19 provided the best succinate production among all the combination.